2005
DOI: 10.1152/ajpheart.01213.2004
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular response to static handgrip exercise: sympathetic vs. autoregulatory control

Abstract: Static exercise causes activation of the sympathetic nervous system, which results in increased blood pressure (BP) and renal vascular resistance (RVR). The question arises as to whether renal vasoconstriction that occurs during static exercise is due to sympathetic activation and/or related to a pressure-dependent renal autoregulatory mechanism. To address this issue, we monitored renal blood flow velocity (RBV) responses to two different handgrip (HG) exercise paradigms in 7 kidney transplant recipients (RTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…4 Catheter-based renal denervation (RD) has been introduced into clinical practice to selectively denervate efferent and afferent renal sympathetic fibers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 Catheter-based renal denervation (RD) has been introduced into clinical practice to selectively denervate efferent and afferent renal sympathetic fibers.…”
mentioning
confidence: 99%
“…1 There is a linear correlation between blood pressure levels and loss in glomerular filtration rate. 2 Doppler sonographic renal resistive index (RRI) reflects systemic and renal hemodynamics, arterial compliance, and pulse pressure 3,4 and has been associated with progression of renal impairment, as well as morbidity and mortality in hypertensive patients. 5 Increased sympathetic tone is an important factor related to the progression of renal disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The autoregulation of renal blood flow, which is caused by the myogenic response and tubule glomerular feedback, enables the kidney to maintain solute and water regulation independent of wide fluctuations of arterial blood pressure. 4 However, because transplanted kidneys were already considered functionally denervated and ischemic, the autoregulation is at a certain degree impaired. Therefore, mean arterial pressure is very important in oxygenation and acidosis and subsequently renal function postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It was systematically described by Charles (Borkovec and O'Brien, 1977), Lerner (Momen et al, 2005), and Etzel (Etzel et al, 2006) have reported an increase in heart rate (HR) during fear. HR changes are in response to the activation or suppression of the cardiac autonomic nervous system (ANS), which is synergistically mediated by the cardiac sympathetic and parasympathetic systems (Guo and Zhang, 2007).…”
Section: Introductionmentioning
confidence: 99%